2019
DOI: 10.4103/ijcm.ijcm_23_19
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression among students of a dental tertiary care center in Kerala

Abstract: Introduction:According to the World Health Organization, more than 300 million people were estimated to suffer from depression in 2017. Many studies have observed that medical personnel have a higher level of depression, but studies among dentists are scarce. Early diagnosis will help in controlling the morbidity and mortality due to depression. Hence, this study was undertaken to estimate the prevalence of depression among students of Government Dental College (GDC), Thiruvananthapuram, the capital city of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Before the pandemic, the contributing factors to depression were closely associated with relationship status and satisfaction in dentistry. 16 In this study, during the COVID-19 lockdown, depression among 60% of the students was associated with worry about professional growth due to reduced clinical training. Furthermore, potential professional growth, concern about clinical experiences and research experience, and other factors such as employment prospects are attributed to depression in 42, 53, and 60%, respectively.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Before the pandemic, the contributing factors to depression were closely associated with relationship status and satisfaction in dentistry. 16 In this study, during the COVID-19 lockdown, depression among 60% of the students was associated with worry about professional growth due to reduced clinical training. Furthermore, potential professional growth, concern about clinical experiences and research experience, and other factors such as employment prospects are attributed to depression in 42, 53, and 60%, respectively.…”
Section: Discussionmentioning
confidence: 62%
“…Deficient clinical training, especially among interns (unable to fulfil the clinical quota, increased course completion length), will indeed be detrimental for professional growth and future employment. 16 17 A previous history of mental health problems also showed a significant association with depression among students. The findings of our study are similar to those of previous studies in which a previous history of mental health problems was associated with the current status of depression.…”
Section: Discussionmentioning
confidence: 91%
“…Similarly, in a research carried out by Raghunathan et al among 364 Indian dental students, more female (28.4%) than male (20.8%) were screened positive for depression and the difference wasn't statistically significant. [12] In a study conducted by Galan et al among dental students enrolled at School of Dentistry of Seville, Spain gender was found to have no significant influence on the prevalence of depression. [9] Our research didn't find a link between the year of dental university education and depressive symptoms.…”
Section: Discussionmentioning
confidence: 92%
“…[4] Many risk factors contributing do occurrence of depressive symptoms among dental students can be distinguished, among others: female gender, problems with class friends, relationship problems, anticipation of family, peer pressure, lack of interest in profession, low satisfaction of relations with peers or academic teachers. [2,4,5,6] Whereas it was concluded that high or medium level of satisfaction from dentistry and close friends protects from emergence of depressive symptoms. [5] Additional factors that can influence the emergence of depression among dental students are internet addiction and lack of musical activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation